GE_GERICHTE P/11066/2015 vom 26. September 2016 - GE Cour de justice (2016)
ANNONCE D'APPEL ; MOTIVATION DE LA DEMANDE ; MOTIVATION DE LA DÉCISION ; DÉCISION D'IRRECEVABILITÉ | CPP.399; CPP.399; CPP.82